Contrast agents and ionization with respect to safety for patients and doctors - Von Tengg-Kobligk, Hendrik; Kara, Levent; Klink, Thorsten; Khanicheh, Elham; Heverhagen, Johannes T.; Böhm, Ingrid B. (S. Karger AG, 2015)
In hemodialysis patients, radiographic imaging with iodinated contrast medium (ICM) application plays a central role in the diagnosis and/or follow-up of disease-related conditions. Therefore, safety aspects concerning ICM administration and radiation exposure have a great impact on this group of patients. Current hardware and software improvements including the design and synthesis of modern contrast compounds allow the use of very small amounts of ICM in concert with low radiation exposure. Undesirable ICM side effects are divided into type A (predictable reactions such as heat feeling, headache, and contrast-induced acute kidney injury, for example) and type B (nonpredictable or hypersensitivity) reactions; this chapter deals with the latter. The first onset cannot be prevented. To prevent hypersensitivity upon reexposure of ICM, an allergological workup is recommended. If this is not possible and ICM is necessary, the patient should receive a premedication (H1 antihistamine with or without corticosteroids). Current imaging hardware and software improvements (e.g. such as additional filtration of the X-ray beam) allow the use of very small amount of ICM and small X-ray doses. Proper communication among the team involved in the treatment of a patient may allow to apply imaging protocols and efficient imaging strategies limiting radiation exposure to a minimum. Practical recommendations will guide the reader how to use radiation and ICM efficiently to improve both patient and staff safety.
CRIS-Team Scopus Importer:2024-12-04